Hak Pakai Atas Tanah Taman Sriwedari: Tumpah Tindih Regulator dan Pemohon Hak Atas Tanah - Selvie Novitasari (Jurnal Hukum Lex Generalis, 2024)
Court decisions on Sriwedari park land disputes from 1970 to 2021 always favored the heirs of KRMT Wiryodiningrat as the legal owner of HGB No. 22 Sriwedari park. The research found that the HGB was obtained in 1965, before the HGB period ended, an extension was submitted. In the midst of the Sriwedari park land dispute and the submission of the HGB extension from the heirs of KRMT Wirjodiningrat who must get a recommendation from the Solo City Government as the supervisor of the issuance of land rights as well as the regulator, the right to use was born from the Solo City Government. When he had to provide a recommendation for the HGB extension, he did not do so but was able to issue a right of use in his name. On the same land, Taman Sriwedari, the Solo City Government acts as the regulator and supervisor of the issuance of land rights and at the same time as the applicant for the issuance of a hak pakai in its name. There is an overlap of functions/roles of the City Government and a conflict of interest that ultimately favors the issuance of the right of use on behalf of the regulator who is also the applicant for the right. The research method used is normative legal research with a statutory approach.